2021
DOI: 10.1111/luts.12394
|View full text |Cite
|
Sign up to set email alerts
|

Is intravesical prostatic protrusion associated with more complications in benign prostatic hyperplasia patients?

Abstract: Objective Intravesical prostatic protrusion (IPP) is a noninvasive parameter that can predict disease progression and development of complications in benign prostatic hyperplasia (BPH). This study was to determine the relationship between IPP and the presence of complications in BPH patients. Methods This was a cross‐sectional study of BPH patients at Enugu State University of Science and Technology Teaching Hospital, Enugu. Patients were assessed for acute urinary retention (AUR), chronic urinary retention (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…All of the studies cited above have shown that higher IPSS correlated with many factors, which indicated more severity of BPH symptoms. Moreover, there are many reports of an association between factors relating to BPH severity; such as intravesical prostatic protrusion 11 , post-void residual urine 2 , prostate volume 12 , the elevation of PSA level 12 and complications of BPH. From the studies above, IPSS may be expected to predict severity the and complications of BPH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the studies cited above have shown that higher IPSS correlated with many factors, which indicated more severity of BPH symptoms. Moreover, there are many reports of an association between factors relating to BPH severity; such as intravesical prostatic protrusion 11 , post-void residual urine 2 , prostate volume 12 , the elevation of PSA level 12 and complications of BPH. From the studies above, IPSS may be expected to predict severity the and complications of BPH.…”
Section: Discussionmentioning
confidence: 99%
“…Each question has zero to five points (0 as no symptom to 5 as almost always suffering from symptoms). The summation of IPSS will classify the severity of symptoms into three groups: mild (0-7), moderate (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and severe (20-35). The sample size in this study was determined by the detection of a 5% difference in the prevalence of BPH in Thailand, with 5% α-error, 20% β-error and 80% power of test.…”
Section: Introductionmentioning
confidence: 99%
“…IPP > 10 mm appears to be associated with more BOO on UDS examination, higher IPSS, higher postvoid residual and a higher rate of acute UR. 20,21 Finally, and surprisingly, although some studies have attempted to determine which urodynamic parameters may predict outcomes after BORRS, there are no robust data from prospective studies identifying UDS parameters, particularly ICS-BOO index (ICS-BOOI) and ICS detrusor contractility index (ICS-DCI) as independent predictors of acute UR or of the need for surgery. This is likely due to the multifactorial nature of the risk for acute UR.…”
Section: Psa As a Predictive Factor For Acute Urmentioning
confidence: 99%
“…A previous study suggested more than half of men with age over 60 years old showed symptoms associated with BPH [ 2 ]. As the disease progresses, symptoms such as hematuria, urinary system infection, urinary calculus and bladder decompensation may occur [ 3 ]. Currently, many surgical methods are available for the treatment of BPH, such as transurethral resection of the prostate (TURP), simple prostatectomy, transurethral laser vaporization and enucleation [ 4 ].…”
Section: Introductionmentioning
confidence: 99%